Flaky Tail Mouse as a Novel Animal Model of Atopic Dermatitis: Possible Roles of Filaggrin in the Development of Atopic Dermatitis - Moniaga, Catharina Sagita; Kabashima, Kenji (IntechOpen, 2012)
None